2022
DOI: 10.1101/2022.11.30.518622
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adult neurogenesis improves spatial information encoding in the mouse hippocampus

Abstract: Adult neurogenesis is a unique form of neuronal plasticity in which newly generated neurons are integrated into the adult dentate gyrus in a process that is modulated environmental stimuli. Adult-born neurons can contribute to spatial memory but it is unknown whether they alter neural representations of space in the hippocampus. Using in vivo two-photon calcium imaging, we found that mice that were previously housed in an enriched environment, which triggers an increase in neurogenesis, had increased spatial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 82 publications
(133 reference statements)
1
9
0
Order By: Relevance
“…The increased spatial tuning of CA3 place cells in the enriched rats suggests that EE leads to more selective and more precise spatial information encoding in CA3, which could support better spatial memory. Combined with recent reports of enrichment-dependent increases of spatial tuning and spatial information in DG mature granule cells in novel environments 38 , these findings show that EE has clear effects on spatial tuning of place cells in the DG/CA3 network. Interestingly, our results stand in contrast to findings from CA1 28 which suggests that EE’s effects on spatial tuning of place cells might be limited to DG/CA3.…”
Section: Discussionsupporting
confidence: 80%
“…The increased spatial tuning of CA3 place cells in the enriched rats suggests that EE leads to more selective and more precise spatial information encoding in CA3, which could support better spatial memory. Combined with recent reports of enrichment-dependent increases of spatial tuning and spatial information in DG mature granule cells in novel environments 38 , these findings show that EE has clear effects on spatial tuning of place cells in the DG/CA3 network. Interestingly, our results stand in contrast to findings from CA1 28 which suggests that EE’s effects on spatial tuning of place cells might be limited to DG/CA3.…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies found that hippocampal activity in area CA3 becomes elevated during aging ( 18, 27 ). We determined single-cell calcium activity by measuring the area under the curve of transients and normalizing to the distance run by each mouse ( 28 ) (Fig. 1E-G).…”
Section: Resultsmentioning
confidence: 99%
“…Single-cell calcium activity was determined as previously described ( 58 ). Briefly, ΔF/F data was filtered with a zero phase shift, third order Butterworth lowpass filter.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations